Pru p 3‐Glycodendropeptides Based on Mannoses Promote Changes in the Immunological Properties of Dendritic and T‐Cells from LTP‐Allergic Patients - Palomares, Francisca; Ramos‐Soriano, Javier; Gomez, Francisca; Mascaraque, Ainhoa; Bogas, Gador; Perkins, James Richard; Gonzalez, Miguel; Torres, Maria Jose; Diaz‐Perales, Araceli; Rojo, Javier; Mayorga, Cristobalina (Molecular nutrition & food research, 2019)
Scope Glycodendropeptides (GDPs) functionalized with mannose can enhance allergen interaction with dendritic cells (DCs) via C‐type lectin receptors (CLRs), modulating the immune response. They can present multiple peptides and have potential applications for diagnosis and treatment of food allergy (FA). The immune response induced by GDPs with mannose and Pru p 3 peptides (mono/tetravalent) with ester (D1ManPrup3/D4ManPrup3) or ether linkers (D1Man‐O‐Prup3/D4Man‐O‐Prup3) in lipid‐transfer‐protein‐allergic patients and tolerant controls is analyzed. Methods and results The immunological response induced by GDPs is studied by assessing monocyte‐derived‐DC maturation, lymphocyte proliferation, cytokine production, and basophil response by flow cytometry. DnManPrup3 was recognized by DCs via CLRs inducing DC maturation in all subjects. However, CCR7 expression is significantly upregulated in allergic patients compared to tolerant controls. These changes correlate with lymphocyte proliferation and specific production of Th2/Th1 cytokines in allergic patients. Moreover, D1ManPrup3 does not induce basophil activation. Conclusion DnManPrup3 induces changes in DC maturation and lymphocyte proliferation, indicating specific recognition via CLRs. Prup3‐GDPs are recognized by immune cells, inducing a specific immune response and modulating the immunological response in FA patients. The specific geometry of D1ManPrup3 in particular makes it a potential candidate for specific immunotherapy development. Prup3‐Glycodendropepetides are recognized by dendritic cells via C‐type lectin receptors stimulating an immunological response in peach allergic patients. The differences in the geometry and chemical nature of the Prup3‐Glycodendropepetides suggest that D1ManPrup3 induces dendritic cell maturation and a proliferative response without activating the basophil response compared to D4ManPrup3, suggesting D1ManPrup3 is a promising candidate for developing therapeutic tools.